Fluktuasi indeks harga saham industri jasa sektor property dan real estate dengan determinan faktor ekonomi makro - Muhammad Fiqhuddin Jazuli; Iramani Iramani (STIE Perbanas Surabaya, 2017)
Capital market have very important macroeconomic’s indicator for a country. The purpose of this study is to examine the effect of macroeconomic factors to the stock price index of property and real estate. In this study used purposive sampling method as determining the sample and multiple linear regression analysis. The result is in a whole inflation, interest rate, balance of payments, and Gross Domestic Product have significant effect to Stock Index Property and Real Estate Sector. Partially, inflation has a negative significant effect on the Stock Price Index, while interest rates, Balance of Payments and Gross Domestic Product have no effect.